PTU-262 Alcohol-misuse and inpatient detoxification: the increasing workload and impact of an alcohol care team and alcohol specialist nurse (ASN) in a district general hospital. (28th May 2012) - Beckett, V L; Ching, J; Wood, V; Singh, G
Abstract : Introduction: The prevalence of alcohol misuse has risen dramatically over the past decade with younger individuals (aged 16–44 years) and women increasingly affected. 1 In 2007 24% adults were classified as hazardous drinkers (33% men, 16% women). 2 Over a 15-year period hospital admission rates for alcohol-related disorders have doubled, 3 with significant social and economic consequences. Recently, The British Society of Gastroenterology and NICE recommended an Alcohol Care Team including an ASN in every District General Hospitals to ensure early and effective inpatient treatment of patients with alcohol misuse; maximising compliance and reducing relapse. Studies indicate that an ASN generates 400 fewer admissions per year with shorter durations of stay and lower mortality rates. 4 Methods: We retrospectively audited the impact of the ASN on rates of inpatient referrals and medical detoxification regimes undertaken between 2004 and 2011 at Bassetlaw District General Hospital. Rates of commenced and completed detoxifications in addition to self-discharge data were obtained. Medical and surgical inpatients were included. Exclusion criteria: outpatient and A&E attendances, telephone referrals. Results: Between 2004 and 2011 the number of inpatient referrals for medical detoxification increased BY 657% (49–371 referrals per year). On average, the majority of inpatients were male (66%) and 48 years of age (range 17–90 years). Over a 7-year period the number of inpatient detoxifications commenced increased by 600% (24–168 detoxifications per year). Similarly, completed detoxifications increased by 517% (23 and 142 completed detoxifications in 2004 and 2011 respectively). On average 90.8% (714/786) detoxifications were completed prior to discharge. 9.2% (72/786) patients self-discharged prior to completing the detoxification regime. Conclusion: The workload of the Alcohol Care Team and ASN has increased substantially over a 7-year period, reflecting the rising prevalence of alcohol misuse and alcohol-related disease. The ASN provides early recognition and implementation of medical detoxification regimes for inpatients, offering support and continuity of care to maximise compliance and efficacy of treatment. Greater recognition and investment in alcohol services is essential within all UK District General Hospitals to minimise the growing burden of alcohol misuse. Competing interests: None declared. References: 1. BMA Board of Science . Alcohol Misuse: Tackling the UK Epidemic. 2008. 2. NHS Information Centre . Statistics on Alcohol . 2010. 3. Institute of Alcohol Studies . The Impact of Alcohol on the NHS . 2009. 4. NHS Evidence . Alcohol Care Teams: To Reduce Acute Hospital Admissions and Improve Quality of Care. 2011.